Flood modelling for a data-scarce semi-arid region by using a synthetic unit hydrograph and 1D or 2D hydrodynamic model. (29th March 2022) - Shaikh, M.P.; Yadav, S.M.; Manekar, V.L.; Samtani, B.K.
In this study, the semi-arid Rel River Basin was divided into three sub-basins (SW1, SW2, and SW3). For first sub-basin (SW1), a unit hydrograph (UH) was developed using rain gauge data. Snyder's method was used to develop a synthetic UH (SUH) for the remaining two ungauged sub-basins (SW2 and SW3). A storm hydrograph was developed from the UH for SW1 and from the SUH for SW2 and SW3. The storm hydrograph was used to create a one-dimensional (1D) steady hydraulic model and two-dimensional (2D) unsteady hydraulic model. The created models were calibrated and validated using field survey data collected immediately after an extreme precipitation event. Critical cross-sections were identified using the 1D hydraulic model. The flood inundation area was identified using the 2D hydraulic model and geographic information system techniques. Remedial measures suggested on the basis of the observed depth, damages and probable reasons for flooding, field survey and modelling results. The observed flood depths were high in rural areas because the villagers had encroached the floodplains to conduct farming. In the urban areas, natural streams and nullahs had been plugged, which resulted in an increase in the flood depth and flood recession time.